Towards an interdisciplinary approach to the study of emotionality in audible speech - L.V. Velichkova; O.V. Kirshinova (Язык и текст, 2025)
Context and relevance. Emotionality is one of the most relevant subjects of research at this stage of development in the humanities. Data from areas actively researching emotionality are not integrated into a single mechanism for analyzing spoken language. This paper analyses scientific sources from the perspective of the physiological and psychological determinants of the emergence of emotion in speech, based on the work of leading Russian researchers in the field of physiology and speech activity theory. Problem. The fragmentation of research on emotionality and the means of its expression in speech from the perspective of different disciplines. Objective. To describe a strategy for an interdisciplinary approach to the study of emotionality in speech. Methods and materials. Based on the study of data from physiology, psychology, psycholinguistics, and linguistics, a conclusion is made about the units of speech that respond to the state of the speaker. Such a unit is taken to be a rhythmic group identified in the course of psycholinguistic analysis of speech perception. To characterize the rhythmic parameters of speech, it is necessary to define the rhythmic unit (rhythmic group / RG) based on a set of characteristics: the size of the rhythmic group in syllables, the position of the stressed syllable, the nature of the stress, and the nature of the relationship between stressed and unstressed syllables. The experimental material consisted of ritual songs in two languages – Russian and German. Rhythmic parameters signal the overall emotional tension of speech. Calm (unemotional) Russian speech is characterized by an even distribution of stressed syllables with a distance of 2-3 syllables. In less tense speech, stress usually falls on syllables in the middle of a phrase, with the culminating stress on the last syllable. Violation of these patterns creates an impression of irritation, threat, and other negative impressions. In German speech, the frequency of stressed syllables exceeding the average indicates an increase in emotional tension and, in general, the negative nature of this tension. These accent indicators disrupt the rhythmic pattern of familiar, ‘neutral’ speech and thus create a kind of restless, negative tension. In lines ranging from 5 to 7 syllables, a low degree of tension is conveyed by the position of stresses at the beginning and end of the stanza. Results. In all texts, tension caused by changes in emotional tension can be traced, revealing nationally specific features in formal characteristics. Conclusions. These interdisciplinary data allow us to develop a mechanism for analyzing spoken speech to determine the emotional tension of the speaker.